2016
DOI: 10.1093/jrr/rrw111
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation regulates long non-coding RNAs in human peripheral blood mononuclear cells

Abstract: Long non-coding RNAs (lncRNAs) are non-protein coding transcripts that modulate mRNA and microRNA (miRNA) expression, thereby controlling multiple cellular processes, including transcriptional regulation of gene expression, cell differentiation and apoptosis. Ionizing radiation (IR), a strong cellular stressor, is known to influence gene expression of irradiated cells, mainly by activation of oxidative processes. Whether and how IR also affects lncRNA expression in human peripheral blood mononuclear cells (PBM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…Thus, gene expression changes in saliva have been assessed during radiation treatment for head and neck cancer [ 78 ]. Radiation-induced changes in non-coding RNAs such as miRNAs or recently discovered lncRNAs have also been investigated as potential radiation dosimetry biomarkers [ 79 84 ]. Since new “omics” approaches open the era of big data in biomarker discovery, large-scale proteomics studies have also been used to identify radiation biomarkers in blood [ 85 , 86 ], saliva [ 87 ] or even urine [ 88 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, gene expression changes in saliva have been assessed during radiation treatment for head and neck cancer [ 78 ]. Radiation-induced changes in non-coding RNAs such as miRNAs or recently discovered lncRNAs have also been investigated as potential radiation dosimetry biomarkers [ 79 84 ]. Since new “omics” approaches open the era of big data in biomarker discovery, large-scale proteomics studies have also been used to identify radiation biomarkers in blood [ 85 , 86 ], saliva [ 87 ] or even urine [ 88 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs can be regulated by radiation as it showed radio-resistance in many kinds of cancer cells [26,27]. Researches have also discovered that lncRNAs transcripts were changed because of ultraviolet rays or ionizing radiation in peripheral blood mononuclear cell (PBMC) [28], thymocyte [29] and melanocyte [30]. LncRNA gas5 was discovered in various cancers to play a regulatory role in radiotherapy efficacy [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Further, as reported, it can act as a sponge for many miRNAs, including miR-26a, and miR-145 [ 33 , 34 ]. Studies have demonstrated that TUG1 was expressed in PBMCs and T lymphocytes [ 15 , 16 ]. Software (LncBase Predicted v.2) predicted the binding between TUG1 and miR-214 .…”
Section: Discussionmentioning
confidence: 99%
“…TUG1 has been considered as an oncogene in many tumor cells [ 13 , 14 ]. Recent studies have demonstrated that TUG1 was expressed in peripheral blood mononuclear cells (PBMCs) and T lymphocytes [ 15 , 16 ]. However, the role of TUG1 in SCI has not been reported.…”
Section: Introductionmentioning
confidence: 99%